Liver-targeted Nano-MitoPBN normalizes glucose metabolism by improving mitochondrial redox balance. (November 2019) - Wu, Meiling; Liao, Lihao; Jiang, Lihan; Zhang, Chunwang; Gao, Hongyang; Qiao, Liang; Liu, Shanlin; Shi, Dongyun
Abstract: Recent advances in Nanomedicine provide promising disease treatment through improved drug delivery efficiency, but clinical applications have encountered difficulties, largely due to the majority of injected nanoparticle is sequestered in liver. In contrast, liver cells seem to be a perfect target for nanoparticles. Here we generated a new formula of liposome encapsulated Nano-MitoPBN as a liver mitochondrial-targeting free radical scavenger. We found that Nano-MitoPBN mainly accumulated in hepatocytes and scavenged hepatic mitochondrial superoxide/hydrogen peroxide generated from mono-electron leak of electron transport chain (ETC) complex I and III. Due to micro-compartmentalization, Nano-MitoPBN increased mitochondrial state 3 respiratory rate and respiratory control ratio (RCR), resulting in decreased NADH:NAD + ratio, improved mitochondrial oxidative energy coupling and ATP synthesis, thus alleviating ROS-induced mitochondrial dysfunction. The functional mitochondria promoted the substrate oxidation by the liver, resulting in increased glycolysis and TCA cycle, which directly speeds glucose decomposition, thus decreasing the peripheral blood glucose level and improving the impaired glucose tolerance in diabetic animals. Our study suggests the potential of liver mitochondrial targeting antioxidative nanomedicines for diabetes mellitus. Graphical abstract: Image 1 Highlights: Liposome encapsulated Nano-MitoPBN is used in liver-targeted therapy. Nano-MitoPBN efficiently scavenges hepatic mitochondrial respiratory-originated ROS. Nano-MitoPBN improves respiration and prevents mitochondrial dysfunction. Nano-MitoPBN increases glycolysis and aerobic oxidation in liver.